Variations in the Molecular and Physiological Characteristics and the Virulence of Monilinia fructicola, M. fructigena and M. laxa Isolates - Pizzuolo, P.H.; Chilosi, G.; Balmas, V.; Aleandri, M.P.; Vitale, S.; Luongo, L.; Corazza, L.; Magro, P. (Phytopathologia Mediterranea, 2006)
Twenty-three Monilinia isolates of various origin were identified and compared by morphological means and by biomolecular protocols based on random amplified polymorphic DNA (RAPD) analysis, and on PCR detection by species-specific primer pairs. The identification of most Monilinia isolates by PCR and RAPD confirmed the identification by morphological criteria, although two isolates initially identified as M. fructigena by morphological means were attributed to M. fructicola by the biomolecular techniques. Monilinia isolates were also compared in terms of their in vitro pectolytic activity and isoenzyme patterns. All the isolates produced polygalacturonase and pectin methylesterase, but pectin lyase activity was found only in M. fructicola and M. fructigena, and not in most M. laxa isolates. The Monilinia isolates differed significantly in their isoenzyme patterns. Based on RAPD-PCR and PCR amplification and pectolytic isoenzymes, the isolates analysed clustered in three major groups, each corresponding to a Monilinia species. Artificial inoculations in peach and pear fruits revealed differences in virulence between the Monilinia species and within isolates. No correlation was found between the amount of pectolytic enzymes produced in vitro and virulence. Variations between and within the Monilinia species may depend at the physiological level on variations in the isoenzyme patterns of the pectolytic enzymes.